Evolution of Forest Policy on Grazing and its Legal Status - Tewari, L. K. (Indian Forester, 1998)
The problem of grazing in forest land was always a matter of prime concern for the foresters. In the absence of a well defined national policy on grazing, this issue was suitably incorporated in progressive forest policies and in laws governing management of forests.